Disparities and implicit bias in the management of low-risk febrile infants: a mixed methods study protocol. Issue 9 (20th September 2022) - Gutman, Colleen K; Lion, K Casey; Aronson, Paul; Fisher, Carla; Bylund, Carma; McFarlane, Antionette; Lou, Xiangyang; Patterson, Mary D; Lababidi, Ahmed; Fernandez, Rosemarie
Abstract : Introduction: The management of low-risk febrile infants presents a model population for exploring how implicit racial bias promotes inequitable emergency care for children who belong to racial, ethnic and language minority groups. Although widely used clinical standards guide the clinical care of febrile infants, there remains substantial variability in management strategies. Deviations from recommended care may be informed by the physician's assessment of the family's values, risk tolerance and access to supportive resources. However, in the fast-paced emergency setting, such assessments may be influenced by implicit racial bias. Despite significant research to inform the clinical care of febrile infants, there is a dearth of knowledge regarding health disparities and clinical guideline implementation. The proposed mixed methods approach will (1) quantify the extent of disparities by race, ethnicity and language proficiency and (2) explore the role of implicit bias in physician–patient communication when caring for this population. Methods and analysis: With 42 participating sites from the Pediatric Emergency Medicine Collaborative Research Committee, we will conduct a multicenter, cross-sectional study of low-risk febrile infants treated in the emergency department (ED) and apply multivariable logistic regression to assess the association between (1) race and ethnicity and (2) limited English proficiency with the primary outcome, discharge to home without lumbar puncture or antibiotics. We will concurrently perform an interpretive study using purposive sampling to conduct individual semistructured interviews with (1) minority parents of febrile infants and (2) paediatric ED physicians. We will triangulate or compare perspectives to better elucidate disparities and bias in communication and medical decision-making. Ethics and dissemination: This study has been approved by the University of Florida Institutional Review Board. All participating sites in the multicenter analysis will obtain local institutional review board approval. The results of this study will be presented at academic conferences and in peer-reviewed publications.